Parkour and the city : risk, masculinity, and meaning in a postmodern sport - Kidder, Jeffrey L. (Jeffrey Lowell), 1977- (Critical issues in sport and society., 2017)
"Parkour is an emerging sport in which practitioners train themselves to move through urban environments in creative and often risky ways. Comprised of a pastiche of stylized movements and dependent on YouTube videos, parkour is quintessentially postmodern, and this book studies parkour from within its sociological context. The book traces the sport's development in Europe, parkour's growth into a worldwide phenomenon, and the meanings local Chicago practitioners have given to the sport. The book explores the dialectical relationship between practitioners' real world activities and global flows of information. It analyzes the city as a site for urban adventure seeking and situates these practices within a discussion of young men's masculine identity claims. Finally, the risk-taking commonly seen in parkour is connected to practitioners' symbolic practices that downplay the dangers of the sport while emphasizing their safety precautions. Instead of pushing the edges of survival, these young people insist they have trained themselves to be highly attuned risk assessors--individuals capable of successfully overcoming challenges of any sort. If urbanism is about the lives individuals lead in the city, parkour represents a unique postmodern interpretation of that way of life"--